Housing Reconstruction After Natural Disasters: A Comparative Review of Modular Box Systems and Traditional Construction in Post-Earthquake Turkey (Case Study: Isias Hotel, Adıyaman) - ALSAJ, ABDULLAH (İstanbul Kültür Üniversitesi, 2025)
Turkey is in an active seismic zone, making it highly vulnerable to earthquakes. This vulnerability was tragically highlighted by the devastating earthquake in February 2023, which heavily impacted several provinces, including Adıyaman. One of the most symbolic losses was the collapse of the Isias Hotel, resulting in significant human and material loss. This thesis explores Modular Box Systems (MBS) as an innovative solution for post-disaster housing reconstruction. A mixed-method approach was adopted, integrating both quantitative and qualitative analyses. Through Multi-Criteria Decision Analysis (MCDA), key factors such as deployment speed, economic viability, durability, seismic resistance, Environmental Adaptability and Maintenance, Cultural and Social Adaptability, and Logistical Challenges were assessed. A case study focusing on the reconstruction of the Isias Hotel area demonstrates the comparative advantages of modular systems over traditional construction methods. Findings reveal that MBS can reduce construction time by approximately 60.4% and lower costs by about 27.5%, while offering superior structural performance under seismic stress. Moreover, the Cost-Benefit Ratio (CBR) analysis indicates that Modular Box Systems outperform traditional construction methods by 31%, confirming their economic efficiency in post-disaster recovery. These systems also contribute to environmental sustainability and allow for culturally responsive designs. Despite logistical constraints and regulatory hurdles, the study concludes that successful implementation is possible through early planning, local workforce training, and supportive policy frameworks. This research underscores MBS as a fast, cost-effective, and resilient solution for housing reconstruction in earthquake-affected regions and recommends its integration into Turkey's disaster recovery strategies.
Keywords: Natural Disasters; Modular Box; Earthquake; post-disaster Recovery; Urban Planning; Turkiye